PENGEMBANGAN MEDIA BERBASIS WEB UNTUK MENINGKATKAN PEMBELAJARAN AGAMA ISLAM SD: Pembelajaran Digital, Pendidikan Agama Islam, Aplikasi Berbasis Web, Hasil Belajar, Teknologi Pendidikan - Muhammad Imam Mulyana; Wahyudi Ariannor; Ratna Fitriani; Muhrian Noor (AL-ULUM | JURNAL PENDIDIKAN DAN PENGAJARAN, 2024)
Abstract: This study aims to develop a web-based application as a learning medium for Islamic Religious Education (PAI) for elementary school students to address challenges in conventional teaching methods that lack engagement. The research employed the Research and Development (R&D) method with the ADDIE development model, encompassing the stages of analysis, design, development, implementation, and evaluation. The subjects were sixth-grade students from elementary schools in Banjarbaru City, with data collection conducted through interviews, observations, and literature reviews. Evaluation was carried out using User Acceptance Testing (UAT) and pretest-posttest methods to assess the application’s effectiveness. The findings reveal that the application effectively enhances students’ motivation and learning outcomes, with an average score increase of 10 points. Statistical tests indicated a significant difference between conventional and application-based learning (p < 0.10). The application features interactive audio, animations, and visuals, making the learning process more engaging. UAT results demonstrated that the application meets quality and user comfort standards. This study concludes that integrating technology into PAI learning offers an innovative solution for improving students' understanding of religious values. Further development is recommended, including the addition of interactive features, broader trials, and integration into mobile platforms to enhance application accessibility.